2018
DOI: 10.1097/md.0000000000010793
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AMHR2 and C-KIT in cervical lesions in Uyghur Women of Xinjiang, China

Abstract: AMHR2 might have some correlation with self defense of our body, while c-Kit might link with the potential invasive capacity of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A high occurrence rate of cervical cancer occurs in Chinese Uyghur women; a study has been focused on OXR1 and OXR2 expressions in these women with cervical cancer and in patients with cervicitis [91]. The study showed that OXR2 was overexpressed in women with cervical cancer when compared with those showing cervicitis; however, no difference was found in both groups regarding OXR1 expression [91].…”
Section: Cervical Cancermentioning
confidence: 97%
See 1 more Smart Citation
“…A high occurrence rate of cervical cancer occurs in Chinese Uyghur women; a study has been focused on OXR1 and OXR2 expressions in these women with cervical cancer and in patients with cervicitis [91]. The study showed that OXR2 was overexpressed in women with cervical cancer when compared with those showing cervicitis; however, no difference was found in both groups regarding OXR1 expression [91].…”
Section: Cervical Cancermentioning
confidence: 97%
“…[90] Cervical cancer OXR2 overexpression. [91] Colon cancer OXR1 expression. Orexins promoted apoptosis and decreased tumor volume.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%